Literature review on the history of Indonesia's universal defense system - Brantas Suharyo G.; Nuhfil Hanani; Fadillah Putra; Dhiana Puspitawati (Educenter : Jurnal Ilmiah Pendidikan, 2024)
The debate over the concept of Indonesia's national defense and security system has been a significant topic since independence until the reform era. This article aims to discuss the dynamics of the Universal People's Defense System within the National Defense and Security System from the independence period to the reform era. A documentation study method is used to collect and analyze important documents such as laws, government policies, official reports, and relevant literature. Data analysis is conducted to identify significant changes in the concept and implementation of the National Defense System and its impact on the system's sustainability. Findings indicate that the national defense concept remains relevant and should be maintained. The Universal People's System involves all societal components, territorial integrity, natural resources, and other means, strengthening military and non-military defense integration, increasing respect, and enhancing deterrence. This concept is still valid in the reform era and remains upheld after the 1945 Constitution amendment. The debate on Indonesia's national protection and security system has been a fundamental issue from independence to the reform era, covering national security, protection, safety functions, and policies. Implications for education include integrating national defense topics in schools to foster public awareness and participation, contributing to a well-informed, participatory society.